2014
DOI: 10.1080/15428052.2014.952474
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Assessment of Yelp.Com Users’ Motivations to Submit and Read Restaurant Reviews

Abstract: This article presents a thematic analysis of Yelp.com users' motivations to read and articulate user-generated reviews. This study's purpose was to identify factors of usage, trust, influence, and contribution of restaurant reviews on Yelp.com. This study found that information search reduction and community membership were the greatest factors encouraging Yelp.com use. Respondents reported trusting Yelp.com due to the community aspects of the website and felt they were able to sort out biased reviews easily. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Although online review research has been growing in recent years, there are few studies investigating guests' motives to write positive and negative online reviews on Trip advisor in the tourism industry in general [3,25,26] and in the Egyptian hotel context in particular. In particular, the following research gaps are identified in literature: nations.…”
Section: Problem Statement: Research Rational and Gapsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although online review research has been growing in recent years, there are few studies investigating guests' motives to write positive and negative online reviews on Trip advisor in the tourism industry in general [3,25,26] and in the Egyptian hotel context in particular. In particular, the following research gaps are identified in literature: nations.…”
Section: Problem Statement: Research Rational and Gapsmentioning
confidence: 99%
“…Moreover, Trip advisor Review Express used to easily send optimized review request emails. It delivers an automatic reminder and a detailed dashboard that tracks the performance of each campaign [24,25].…”
Section: Trip Advisormentioning
confidence: 99%
See 1 more Smart Citation
“…Although online review research has been growing in recent years, there are few studies investigating guests" motives to write positive and negative online reviews on TripAdvisor in the tourism industry in general (Cantallops & Salvi, 2014;Parikh, et al, 2015;Zarrad, and Debabi, 2015) and in the Egyptian hotel context in particular. In particular, the following research gaps are identified in literature:…”
Section: Problem Statement: Research Rational and Gapsmentioning
confidence: 99%
“…2. There is a lack of research regarding the motives for posting online opinions and reviews in tourism experiences (Yoo and Gretzel, 2008;Wilson, et al, 2012;Cantallops & Salvi, 2014;Parikh, et al, 2015). However, motives can be traced to other e-WOM studies outside of the tourism industry, and many of these previous studies refer to Hennig-Thurau et al (2004) study as a guideline.…”
Section: Problem Statement: Research Rational and Gapsmentioning
confidence: 99%